RAW MATERIAL INVENTORY CONTROL ANALYSIS IN THE RUBBER PRODUCTION PROCESS AT PTPN XII PERSERO KEBUN KOTTA BLATER - Varuq, Nauval Ilham; Haris Hermawan; Ahmad Izzuddin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate the raw material control system in the rubber production process at PTPN XII Persero Kebun Kotta Blater using the Economic Order Quantity (EOQ) method. Method: Employing a quantitative descriptive analysis approach, the EOQ model was applied to analyze inventory management practices related to rubber latex processing into RSS sheets. Results: The 2023 inventory data revealed that the company’s actual inventory issuance exceeded the optimal EOQ value of IDR 2,883.19, indicating inefficiencies in raw material control. Implementing the EOQ model demonstrated potential cost savings amounting to IDR 885,133,971,190,639 by optimizing order quantities and reducing excess inventory. Novelty: This research highlights the significant financial benefits of applying EOQ in rubber agribusiness, specifically within PTPN XII Kebun Kotta Blater, by providing an empirical assessment of inventory management optimization in the agricultural processing sector. The findings contribute to enhancing operational efficiency and sustainable resource utilization in natural rubber production.